2022
DOI: 10.1111/add.16018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impact of COVID‐19 pandemic‐driven increases in alcohol consumption on health outcomes and hospitalization costs in the United States

Abstract: Background and aims Alcohol consumption increased in the early phases of the COVID‐19 pandemic in the United States. Alcohol use disorder (AUD) and risky drinking are linked to harmful health effects. This paper aimed to project future health and cost impacts of shifts in alcohol consumption during the COVID‐19 pandemic. Design An individual‐level simulation model of the long‐term drinking patterns for people with life‐time AUD was used to simulate 10 000 individuals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…The significant increase in alcohol use during the pandemic had immense implications from a healthcare perspective. A US model projecting increased alcohol use from the first year of the pandemic over 5 years resulted in a loss of 79 000 life years, 332 000 quality‐adjusted life years, and an additional $5.4 billion in healthcare costs, of which $3.0 billion were related to cirrhosis hospitalizations 20 …”
Section: Discussionmentioning
confidence: 99%
“…The significant increase in alcohol use during the pandemic had immense implications from a healthcare perspective. A US model projecting increased alcohol use from the first year of the pandemic over 5 years resulted in a loss of 79 000 life years, 332 000 quality‐adjusted life years, and an additional $5.4 billion in healthcare costs, of which $3.0 billion were related to cirrhosis hospitalizations 20 …”
Section: Discussionmentioning
confidence: 99%
“…We used a validated individual‐level simulation model of the long‐term drinking patterns of US adults with AUD diagnoses (Barbosa et al, 2019, 2023). Individual‐level models (or microsimulation models) simulate one individual at a time and keep track of each simulated individual's history (Neumann et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the nature of the alcohol‐related conditions, each condition was assumed to be acute (i.e., lasting 1 year or less), long‐term (lasting an average of 5 years), or chronic (lasting for the remainder of one's lifetime) in the model. Additional information is available in the Supporting Information and in Barbosa et al (2023).…”
Section: Methodsmentioning
confidence: 99%
“…As already mentioned, many studies have confirmed that an increase in alcohol consumption in a short-term period during the COVID-19 pandemic can cause long-term ArLD-related morbidity, hospitalizations and mortality[ 13 - 15 , 17 , 27 ], and that abnormal liver biochemical tests are often closely related to the severity and prognosis of patients with COVID-19[ 28 ].…”
Section: Alcohol and Liver Injurymentioning
confidence: 99%
“…A simulation model of the long-term drinking patterns of people with lifetime AUD has revealed that if the increase in alcohol consumption registered in the United States in the first year of the pandemic continues with similar characteristics, alcohol-related mortality, morbidity and associated costs will increase considerably over the next 5 years[ 17 ]. These observations are a red flag for the necessary improvement in screening for high-risk alcohol use and optimization of early treatment of abuse or misuse and its physical and psychological consequences.…”
Section: Introductionmentioning
confidence: 99%